REVITALISASI PENDIDIKAN JASMANI MELALUI PENERAPAN MODEL BERMAIN EDUKATIF BERBASIS ALAM DI RA AL IRSYAD KEDUMULYO - Muhammad Lukmanul Khakim; Ahmad Afif Fuddin; Heny Kusmawati (CV. ADIBA AISHA AMIRA, 2023)
Early childhood physical education is a very important aspect in the development of children's cognitive, affective and psychomotor abilities in preparing them to enter the elementary school level. In practice, early childhood physical education has several problems related to learning activities, institutions, social conditions and government policies, where early childhood physical education receives less attention. This research uses a qualitative approach with the case study method which aims to examine the research problem in detail and comprehensively. This research was conducted at RA Al Irsyad Kedumulyo, Sukolilo District, Pati Regency and involved 3 teachers and 29 early childhood children. Survey techniques through interviews, observation and documentation as well as perform data analysis through data reduction, data presentation and inference. The results showed that there were changes in cognitive skills which were characterized by problem solving through group activities, changes in affective skills, which were indicated by a sense of caring, and psychomotor changes which were characterized by early childhood skills through nature-based education. Games and increased interest in early childhood.